Pharmacokinetics, pharmacodynamics and efficacy on pediatric tumors of the glioma radiosensitizer KU60019. Issue 6 (11th August 2014) - Vecchio, Donatella; Daga, Antonio; Carra, Elisa; Marubbi, Daniela; Raso, Alessandro; Mascelli, Samantha; Nozza, Paolo; Garrè, Maria Luisa; Pitto, Francesca; Ravetti, Jean Louis; Vagge, Stefano; Corvò, Renzo; et al.
<x xml:space="preserve">Abstract</x> We have recently reported that glioblastoma (GB)‐initiating cells (GIC) with low expression and/or mutation of TP53 and high expression of PI3K ("responder" genetic profile) can be effectively and safely radiosensitized by the ATM inhibitor KU60019. We report here on drug's diffusion and elimination from the animal body and brain, its effects on orthotopic GB and efficacy toward pediatric GIC. Healthy mice were infused by convection enhanced delivery (CED) with KU60019 and the drug kinetics followed by high performance liquid chromatography–mass spectrometry. Already at the end of CED, KU60019 had diffused from the injection site to the ipsilateral and, to a lower extent, controlateral hemisphere. After 24 hr, no drug could be detected all over the brain or in other organs, indicating rapid draining and excretion. After intraperitoneal injection, traces only of KU60019 could be detected in the brain, indicating inability to cross the brain–blood barrier. Consistent with the induction of cell cycle progression previously observed in vitro, KU60019 stimulated proliferation of orthotopic GB cells with the highest effect observed 96 hr after drug delivery. Adult GIC with high expression of TP53 and low expression of PI3K could be radiosensitized by KU60019, although less promptly than GIC bearing the "responder" profile. Consistent with the kinetics of proliferation induction, the highest radiosensitizing effect was observed 96 hr after delivery of KU60019 to GIC. Pediatric GIC could be similarly radiosensitized after exposure to KU60019. The results indicate that ATM inhibition may allow to radiosensitize a wide range of adult and pediatric high‐grade gliomas.